Designing for Justice: Preparing Culturally Competent Science and Mathematics Teacher Advocates for High-Need Schools - Grillo, Monica; Kier, Meredith (Innovations in Science Teacher Education, 2022)
In a time when the United States is faced with continued racism and social unrest, it is more important than ever to prepare teachers who can advocate for marginalized students and social justice. This article describes the evolution of a seminar course called Theory and Reality: Practicum in Math and Science Teaching in High-Need Schools within the context of a predominately White teacher-preparation program. Guided by scholars of culturally relevant education and our professional and personal journeys as equity-focused teacher educators, we sought to design experiences to prepare preservice science and mathematics teachers to teach in high-poverty or underfunded schools. Specifically, the course was intended to (1) develop an understanding of pedagogical practices and educational strategies for successful teaching in a high-need school setting, especially in mathematics and science classrooms, and (2) cultivate both cultural self-awareness and cross-cultural consciousness in one’s ability to adapt to the high-need environment in a culturally responsive way. We describe the evolutionary rationale for changes made to course assignments and readings to promote cultural competence and early advocacy skills for teacher candidates interested in teaching in schools facing poverty. We highlight preservice teachers’ reflections that evidence their early conceptualizations of teaching in a high-need school context and how assignments promoted their relationship-building and advocacy skills for marginalized students.